Haemonchus contortus: an overview. (6th January 2023) - Carson, Amanda; Reichel, Rudolf; Bell, Suzie; Collins, Rachael; Smith, Jasmine; Bartley, Dave
Abstract : This focus article was prepared by Amanda Carson, Rudolf Reichel, Suzie Bell, Rachael Collins and Jasmine Smith of the APHA Small Ruminant Species Expert Group, and Dave Bartley from the Moredun Research Institute.